Penerapan Metode Simple Additive Weighting (SAW) Dalam Penentuan Jenis Mobil Honda Yang Paling Diminati - Muchamad Ridwan; Ahmad Setiadi; Norma Yunita; Siti Marlina (LPPM Universitas Bina Sarana Informatika, 2019)
For some people, car is no longer a luxury item that is difficult to obtain. Cars are one of the means of effective and efficient daily transportation. The specifications of each Honda car offered at PT Mitrausaha Gentaniaga Puri are very diverse and have advantages and disadvantages in terms of price, fuel consumption, cylinder content, fuel tank capacity, passenger capacity, and Other features. This makes the prospective buyers of Honda cars difficult to determine for themselves which car suits his needs. One method of decision support system that can be used in the Honda car selection at PT Mitrausaha Gentaniaga Puri is the Simple Additive Weighting (SAW) method. The concept of this method is to look for the weighted summation of the performance rating on each alternative of all attributes. An alternative with the largest value is the final result obtained to be used as a consideration for prospective buyers of Honda cars at PT Mitrausaha Gentaniaga Puri and the cars in demand are Mobilio, BRV, and CRV. Keywords : Car, Decision Support System, Simple Additive Weighting